The Correlation between Students' Reading Comprehension of Indonesian Fiction and Their Writing Ability of English Narrative Texts - Eryani , Fauziah; Soraya, Kety (JEDLISH : Journal Of Education and English Language Teaching, 2021)
Better writers tend to be better readers (Stotsky, 1983 in Kroll, 1990). Dealing with this main theory, there is an assumption that many students who like reading fiction (novel/ story) in Bahasa Indonesia, they also get good marks in English writing achievements. Therefore, the researcher interested to investigate whether there is a correlation between students' reading comprehension of Indonesian fiction and their writing ability of English narrative texts. To support this research, there are some related literature and related findings dealing with this research. The research is a correlational study in ex-post facto design. Population of the research is all second grade students. And the random sampling is used to take the sample. The sample includes 42 students. Next, the data is gained through the reading comprehension test, the writing narrative test as the research instruments. The instruments are validated by trying out, consulting the advisors, and so on. The data from those instruments is analyzed by using statistical analysis, the Pearson Product Moment coefficient correlation, since it is in the form of interval data. The data is calculated by using manual calculation, calculation by using Microsoft Excel program and calculation from SPSS (Statistical Product Solution Service) version 14.0 to get valid computation in analysis. The finding of this research shows that r observes = 0.8866>r table=0.3044 at significant level 0.05 with df=40. It means that there is a significant and positive correlation between students' reading comprehension of Indonesian fiction and their writing ability of English narrative texts. In other word, the higher students' reading comprehension of Indonesian fiction tends to be the higher their writing ability of English narrative texts and vice versa. Therefore, it is recommended to students to read Indonesian fiction in order to promote their writing ability. This finding is expected 2 to be able to give much significant contribution to teachers, students, next researchers, and people who are interested in reading-writing connection.